PROSPEK DAN FAKTOR FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR TPT ( TEKSTIL PRODUK TEKSTIL) PROVINSI BALI - Ni Putu Lia Perdana Sari; Gusti Ayu Putu Wulan Rahmasari (Yayasan Nusantara Hasana Berdikari, 2024)
This research aims to analyze the prospects and factors that influence the export volume of TPT (Textile Products) in Bali Province. The data used in this research is quantitative data sourced from BPS data for Bali Province and the data processing tool used is (Eviews 12). The results of the research show that the independent variables jointly influence the dependent variable. The interest rate variable has a significant influence on TPT export volume variable. The exchange rate and export price variables do not have a significant effect on the TPT export volume variable. Several recommendations. The government needs to maintain the stability of the rupiah exchange rate against foreign currencies. This can be done in various ways, such as maintaining the country's foreign exchange reserves, increasing non-oil and gas exports, and reducing imports. The stability of the rupiah exchange rate will provide certainty for business actors in running their businesses. This will encourage them to increase production and exports. The government needs to reduce the level of working capital credit interest rates. This can encourage production in the textile industry and increase export volume. Low working capital credit interest rates will make production costs cheaper. This will encourage the textile industry to increase production and exports. The government needs to improve product quality and design of textile products. This can be done by providing training and assistance to textile industry players.